Bistable [2]rotaxane encoding an orthogonally tunable fluorescent molecular system including white-light emission. Issue 75 (5th September 2018) - Liu, Yue; Zhang, Qi; Jin, Wei-Hang; Xu, Tian-Yi; Qu, Da-Hui; Tian, He
Abstract : By combining a rotaxane-type molecular switch and traditional fluorescent switch, an orthogonally tunable fluorescent molecular system was constructed, which can generate multicolor fluorescence including white light. Abstract : Orthogonally tunable multicolor fluorescence including white-light emission was achieved using a dual-component molecular system. Under external acid/base stimuli, we were able to change the fluorescence of a mixture of two fluorescent molecular switches in an orthogonal and reversible manner, hence generate emission of multiple colors from blue to yellow, including white light (CIE (0.29, 0.34)).